Java and Algorithmic Thinking for the Complete Beginner. - Aristides Bouras; PACKT (GB: Packt, 2024)
Dive into the world of Java and algorithmic thinking with this book. This comprehensive guide for beginners covers everything from basic computer operations to advanced programming concepts. Key Features Introduction to Java & algorithmic thinking with a proper guide from basic to advanced concepts Tips and tricks to enhance programming efficiency, and exercises for real-world application Detailed exploration of control structures, data structures, and subprograms Book Description Begin your programming journey with a comprehensive course designed to introduce you to the world of Java and algorithmic thinking. The course starts by laying a solid foundation with an understanding of how computers work and an introduction to integrated development environments. As you advance, you'll delve into essential Java concepts, learning about variables, constants, and basic algorithmic concepts that are crucial for any aspiring programmer. Moving forward, the course offers a deep dive into more complex topics, including handling input and output, using operators, and creating trace tables. You'll get hands-on experience with Visual Studio Code and explore sequence control structures, manipulating numbers, and crafting complex mathematical expressions. In the final stages, the course covers advanced topics such as data structures, subprograms, and object-oriented programming. You'll learn to manipulate one-dimensional and two-dimensional arrays, work with HashMaps, and understand the intricacies of user-defined subprograms. The course concludes with a focus on file management and offers numerous tips and tricks to enhance your programming efficiency. By the end, you'll have a strong foundation in Java programming and algorithmic thinking, well-prepared to tackle more advanced challenges. What you will learn Understand the fundamentals of how computers work Master Java programming basics and IDEs Develop proficiency in handling operators, and trace tables Implement sequence and decision control structures in programming Manipulate numbers, strings, and complex expressions Utilize arrays, HashMaps, and other data structures effectively Who this book is for This course is perfect for complete beginners with no prior programming experience, including high school students and hobbyists. It is also suitable for those with a basic understanding of computers who wish to deepen their knowledge of Java and algorithmic thinking. Additionally, college students in non-computer science majors, professionals seeking a career change into tech, and educators looking to incorporate programming into their curriculum will benefit from this comprehensive guide. No prerequisites are required, making it accessible to anyone eager to learn.
Data in extended ASCII character set.
Mode of access: Internet.